Fatty acids as suitable biomarkers to assess pesticide impacts in freshwater biological scales – A review - Ana M.M. Gonçalves; Carolina P. Rocha; João C. Marques; Fernando J.M. Gonçalves (Ecological Indicators, 2021)
The toxic effects associated to pesticides have been for long a concern in terms of environmental and human safety. The recognition of the limitations of numerous, if not all, pesticides in terms of species-specificity, toxicity level, persistency in the environment, influencing its runoff and transport ability, among other characteristics, have been the subject of numerous studies over the years. These have especially focused on the deleterious impacts of such substances in non-target organisms, including potential effects in humans, considering pesticide uptake through the ingestion of contaminated foodstuff. Aquatic ecosystems may be considered the most vulnerable to pesticide contamination, has most toxicants may eventually end up in these systems, if not directly, via indirect inputs. Aquatic communities are, thus, susceptible both to on-point acute contaminations and to exposure to mixtures of different contaminants for longer periods. Impacts of numerous pesticides in non-target aquatic species have been reported and investigated, contributing to the definition of regulations and legislation to prevent harmful effects to the communities. However, in order to assess effectively the effect of different pesticides in organisms, the definition of suitable biomarkers is crucial. As one of the most identifiable effect of pesticides is cell damage induced by oxidative stress, most studies have resorted to the analysis of antioxidant enzymes to assess the impacts of contamination in the organism. Nonetheless, with methodological advances, other molecules have been identified as potentially useful to be used as biomarkers, as fatty acids. These ubiquitous macromolecules in living organisms are major constituents of biological membranes and tissues. Evidence of the impact of xenobiotics on lipid metabolism and composition, as well as the sensitivity of fatty acids profiles to alterations in the homeostasis of organisms, have been arising, supporting the suitability of these macromolecules as biomarkers of toxicants exposure. However, most studies using fatty acids as biomarkers have dwelled mostly on marine ecosystems, disregarding other aquatic systems, as freshwater systems. Given the importance of these systems as providers of numerous services and goods and their role in ecological integrity and support, the present literature review aims to compile and critically review the studies conducted until the present time regarding the use of fatty acids as biomarkers of pesticide exposure assessment in freshwater communities, as well as highlight limitations identified and propose future research.